Oral history, health and welfare - Bornat, Joanna (Routledge, 2000)
Oral History, Health and Welfare discusses the significance of oral history to the history of the development of health and welfare provisions. It includes discussion on:* the end of the workhouse * professional education and training of midwives * HIV and Aids * birth control * the role of the community pharmacist * pioneers of geriatric medicine * oral history and the history of learning disability.